CONSPIRACY VS PREDICTION OF DEAN KNOOTZ AGAINST COVID-19: PLOT ANALYSIS AND LITERARY SOCIOLOGY IN THE NOVEL "THE EYES OF DARKNESS" - Mubasyira, Mu'thia; -, Zuriyati; Lustyanie, Ninuk (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2021)
This research was conducted with the aim of finding out how the plot analysis and literary sociology of the novel titled "The Eyes of Darkness" proves the truth of the conspiracy against the emergence of artificial viruses and predictions made by author Dean Koontz on the pandemic situation of the coronavirus outbreak-19 today as depicted in the novel. This research uses descriptive qualitative methods with structural approaches so that it is drawn a thorough and structured analysis. The primary data taken comes from the novel while the secondary data is obtained from a literature study conducted as a reference material to compare the existence of the two viruses, namely the Wuhan-400 virus depicted in the novel and the Corona-19 virus that occurred in the current situation. From the results of the discussion came the conclusion that there are some similarities of the symptoms caused by these two viruses although there are differences in the rate of death caused. In addition, the social situation of the people depicted in the novel also has similarities with the situation when the Covid-19 pandemic broke out. This is seen from the comparison of the economic side of society and the political turmoil that occurs.